Vibrational studies of calcium magnesium ultraphosphate glasses - Hussin, Rosli; Salim, Musdalilah Ahmad; Alias, Nur Shahira; Abdullah, Mutia Suhaibah; Abdullah, Suhailah; Ahmad Fuzi, Siti Aishah; Hamdan, Sinin; Md. Yusuf, Mohd. Nor (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia, 2009)
Phosphate glasses in a system of magnesium calcium phosphate for host matrix luminescent materials were investigated. The glass samples in a series of xMgO–(40- x)CaO–60P2O5 in molar ratio (0 ? x ? 40 mol%) were prepared using melt-quenching technique. The effect of Mg and Ca content on the structure and glass stability against crystallization in the system of MgO–CaO–P2O5 ultraphosphate has been investigated using XRD, Infrared and Raman spectroscopy. The compositions containing up to 40 mol% of CaO and /or MgO formed glasses and no crystalline phases were detected by XRD. The results of IR and Raman spectroscopy suggest that the phosphate network of these glasses is composed of middle (Q2) and branching (Q3) phosphate tetrahedral and other calcium/magnesium anions. All the symmetric and asymmetric stretching vibrations of POP and PO2 observed in the spectra are characteristic of Q3 and Q2 groups. The glass network, especially the Q2 units can be modified by the presence of Ca and Mg ions. This modification is primarily associated with the phosphate and the Q2 and Q3 phosphate units randomly distributed in the network. Spectroscopic results shows that the modification of the phosphate network is higher for the Ca containing glasses with respect to the Mg ones, at the same alkali earth content, due to the well defined Ca properties as a modifying cation. Formation of P–O–H bond expresses the hygroscopic nature of the phosphate glasses. This study shows that the vibrational spectroscopy (Infrared and Raman) are provide useful, complementary information about the network structures of ultraphosphate glasses